Pedagogical educational environmental management for water resource management in public educational institutions of El Agustino, Lima-Peru. - Giles Casas, Ana María (2013)
The present investigation is focused on whether the pedagogical educational environmental management related to the management of water resources of the state schools in the district of “El Agustino” due tolittle analysis of water issues. Through the development of the program of learning units within a system of mainstreaming in vironmental management of water resources, allows to acquire a level o f culture and undertake sustainable actions.This research is descriptive correlational, because through observation, comparison and analysis of the variables is established pedagogical relationship between en vironmental management and water resource management, holding theresults of a questionnaire and checklist.                          Therefore, it is recommended to promote the educational development of environ mental management of water resources for all institutions.